Short Communication: Phytochemical screening and toxicity of ethanol extract of Sauropus androgynus - AWALUDIN AWALUDIN; KARTINA KARTINA; DIANA MAULIANAWATI; WASMEN MANALU; ANDRIYANTO ANDRIYANTO; RIKA SEPTIANA; AGUS ARFANDI; YUBAL LALANG (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Awaludin, Kartina, Maulianawati D, Manalu W, Andriyanto, Septiana R, Arfandi A, Lalang Y. 2020. Short Communication: Phytochemical screening and toxicity of ethanol extract of Sauropus androgynus. Biodiversitas 21: 2966-2970. Katuk (Sauropus androgynus L.) (SAL) is a plant used to increase the production of breast milk for nursing mothers and lactating mammalian animals because this plant contains high sterols. Phytosterols are plant sterols known to play a role in the synthesis and secretion of progesterone and estradiol.  Progesterone and estradiol are hormones that are involved in controlling the reproduction and mammary gland growth and development in mammalian animals. Estradiol also stimulates vitellogenin synthesis in oviparous animals such as avian and fish.  The study was designed to determine the phytochemical contents and the level of toxicity of the SAL ethanol extract. The research was conducted in 4 phases i.e., (i) extraction of SAL samples using ethanol 70%, (ii) the analysis of phytochemical content of SAL extract using GCMS, (iii) toxicity test of SAL extract in giant tiger shrimp larvae, and (iv) data analysis. The results of GCMS analysis showed that the SAL extract was dominated by the fatty acid group (62.92%), phenol (15.3%), and terpenoids (4.03%). These compounds have roles in animal reproduction and production. The mortality data of giant tiger shrimp larvae were analyzed using probit analysis to determine the LC50 of ethanol extract of SAL. The results of toxicity test for 24 hours showed that the LC50 of the ethanol extract of SAL was 552.208 mg/L. The phytochemical analysis showed that SAL extract has dominant concentrations of fatty acid, phenol, and terpenoid that could be used to improve the reproduction and production of fish.